Applying orbital multi-angle photopolarimetric observations to study properties of aerosols in the Earth's atmosphere: Implications of measurements in the 1.378 µm spectral channel to retrieve microphysical characteristics and composition of stratospheric aerosols. (March 2021) - Dlugach, Janna M.; Mishchenko, Michael I.; Veles, Oleksandr A.
Highlights: The possibility of retrieving microphysical characteristics and composition of stratospheric aerosols on the basis of orbital multi-angle photopolarimetric measurements performed in the 1.378-µm spectral channel is studied. Numerical modeling of the Stokes parameters is performed for aerosols with various optical characteristics. A comparison of the sensitivity to the aerosol properties of photopolarimetric measurements of various accuracy is carried out. Abstract: We analyze the possibilities of orbital photopolarimetric measurements to study properties of aerosols in the Earth's atmosphere. As an example, we consider the case when such measurements are performed within a narrow spectral channel centered at 1.378 µm that allows to retrieve microphysical characteristics of stratospheric aerosols separately from those of tropospheric aerosols. We consider the case of stratospheric aerosols caused by volcanic eruption, and adopt the model of the stratosphere in the form of a homogeneous plane-parallel layer composed of polydisperse spherical particles. We use numerically exact solutions of the vector radiative transfer equation to theoretically simulate measurements carried out at various numbers of scattering angles, including: (i) radiance measurements alone; (ii) polarization measurements alone; and (iii) radiance and polarization measurements together. The results of computations show that the simultaneous use of radiance and polarization measurements at a sufficiently large number of scattering angles enables one to retrieve the optical thickness, effective radius, and refractive index of aerosols with adequate accuracy. We demonstrate how the accuracy of the derived values of the optical parameters of aerosols depends on the accuracy of measurements of the intensity and polarization of the reflected light, optical thickness of aerosol layer itself, effective radius of aerosols, width of the particle size distribution, and number of viewing angles.